Socially-pedagogical work with adolescents of deviant behavior from unfavorable families - Акрамова, Алия; Шайсултанова, Асель (Pedagogy and Psychology, 2021)
The article deals with the problem of deviant adolescents. With the theory and practice of pedagogy and psychology, it becomes necessary to study this topic not only by psychologists, but also by lawyers, social workers, and doctors. The authors presented a review of foreign literature on the problem of deviant behavior, methods and ways of changing the behavior of adolescents, as well as the biological and hereditary causes of this phenomenon. The authors draw attention to the influence of family forms of upbringing, leading to antisocial and deviant behavior. The family’s unhappiness is one of the main factors of deviations in the social, psychological, pedagogical development of the child. The article describes the styles of relationships in the family that can lead to the formation of incorrect social behavior in adolescents, an analysis of social and pedagogical work with adolescents of deviant behavior is given.